FOREIGN DIRECT INVESTMENTS DURING THE CORONOMIC CRISIS AND ARMED CONFLICT IN THE NEIGHBOURHOOD, CASE OF GEORGIA (Globalization and Business, 2023)
The paper provides an analysis of FDI challenges and their impact on the service sector of Georgia, during the covid-19 global pandemic, along with the armed conflict factor in Eastern Europe, between Ukraine and Russia. The article also discusses issues such as public debt, economic growth, employment, international rankings, trade, tourism, etc. Since the cases of different countries vary according to their economic structure, political reality, and even the readiness to overcome those newest and unprecedented challenges, the case of Georgia provides a great example of a small, democratic, developing economy, which significantly depends on foreign direct investments both inward and outward, regional stability and not the least - western cooperation and support.